Exploring The Implementation Challenges of Inclusive Education Policies in Primary Classroom Practices - Totini, Anjum Tasnim; Fuad, A Z M; Alam, Md Nurkutubul (South Asian Journal of Social Sciences and Humanities, 2025)
This study delves into the implementation challenges of inclusive education policies, highlighting the major factors of not assuring inclusiveness and quality in the Bangladeshi primary classroom context. This study engaged in exploring the gaps and why the implementation of the policies has not been considered properly. Data for this study was collected from four primary schools using semi-structured interviews of a head teacher and a teacher from each of four schools, classroom observation (approximate 40-45 students in a classroom), and thematic analysis was employed to analyze the data sets. The findings reveal gaps in teachers, administrators, and students’ awareness as they have limited knowledge of inclusive education principles and limited stakeholder engagement. Classroom observation also reveals insufficient inclusive-practice in classrooms to accommodate children with special needs, with inadequate teacher training and lack of cooperation from stakeholders which affect communication engagement for special needs children. This study implies that the authorities should create some specific opportunities both for the teachers and students to implement inclusiveness and its practice in the classroom.